Bone morphogenetic protein‐2, ‐6, and ‐7 differently regulate osteogenic differentiation of human periodontal ligament stem cells. Issue 1 (13th July 2013) - Hakki, Sema S.; Bozkurt, Buket; Hakki, Erdogan E.; Kayis, Seyit Ali; Turac, Gizem; Yilmaz, Irem; Karaoz, Erdal
Abstract The utility of adult stem cells for bone regeneration may be an attractive alternative in the treatment of extensive injury, congenital malformations, or diseases causing large bone defects. To create an environment that is supportive of bone formation, signals from molecules such as the bone morphogenetic proteins (BMPs) are required to engineer fully viable and functional bone. We therefore determined whether BMP‐2, ‐6, and ‐7 differentially regulate the (1) proliferation, (2) mineralization, and (3) mRNA expression of bone/mineralized tissue associated genes of human periodontal ligament stem cells (hPDLSCs), which were obtained from periodontal ligament tissue of human impacted third molars. hPDLSCs from six participants were isolated and characterized using histochemical and immunohistochemical methods. A real‐time cell analyzer was used to evaluate the effects of BMP‐2, ‐6, and ‐7 on the proliferation of hPDLSCs. hPDLSCs were treated with Dulbecco's modified Eagle's medium containing different concentrations of BMP‐2, ‐6, and ‐7 (10, 25, 50, 100 ng/mL) and monitored for 264 hours. After dose‐response experiments, 50 and 100 ng/mL concentrations of BMPs were used to measure bone/mineralized tissue‐associated gene expression. Type I collagen, bone sialoprotein, osteocalcin, osteopontin, and osteoblastic transcription factor Runx2 mRNA expression of hPDLSCs treated with BMP‐2, ‐6, and ‐7, were evaluated using quantitative RT‐PCR. Biomineralization of hPDLSCs was assessed using von Kossa staining. This study demonstrated that BMPs at various concentrations differently regulate the proliferation, mineralization, and mRNA expression of bone/mineralized tissue associated genes in hPDLSCs. BMPs regulate hPDLSC proliferation in a time and dose‐dependent manner when compared to an untreated control group. BMPs induced bone/mineralized tissue‐associated gene mRNA expression and biomineralization of hPDLSCs. The most pronounced induction occurred in the BMP‐6 group in the biomineralization of the hPDLSCs. Our data suggest that BMP‐2, ‐6, and ‐7 are potent regulators of hPDLSC gene expression and biomineralization. Employing BMPs with hPDLSCs isolated from periodontal ligament tissues provides a promising strategy for bone tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 119–130, 2014.